Distribution and Structure of DM2 Repeat Tract Alleles in the German Population - Mahyera, Alexis S.; Schneider, Tamara; Halliger-Keller, Birgit; Schrooten, Katja; Hörner, Eva-Maria; Rost, Simone; Kress, Wolfram (Frontiers in Neurology, 2018)
Autosomal dominant inherited Myotonic dystrophy type 1 and 2 (DM1 and DM2) are the most frequent muscle dystrophies in the European population and are caused by repeat expansion mutations. For Germany cumulative empiric evidence suggests an estimated prevalence of DM2 of roughly 9 in 100,000, therefore being as prevalent as DM1. In DM2, a (CCTG)n repeat tract located in the first intron of the CNBP gene is expanded. The CCTG repeat tract is part of a complex repeat structure comprising not only CCTG tetraplets but also repeated TG dinucleotides and TCTG tetraplet elements as well as NCTG interruptions. Here, we provide the distribution of normal sized alleles in the German population, which was found to be highly similar to the Slovak population. Sequencing of 34 unexpanded healthy range alleles in DM2 positive patients (heterozygous for a full expansion) revealed that the CCTG repeat tract is usually interrupted by at least three tetraplets which according to current opinion is supposed to render it stable against expansion. Interestingly, only the largest analyzed normal allele had 23 uninterrupted CCTGs and consequently could represent an instable early premutation allele. In our diagnostic history of DM2 cases, a total of 18 premutations were detected in 16 independent cases. Here, we describe two premutation families, one with an expansion from a premutation allele and the other with a contraction of a full expansion down to a premutation allele. Our diagnostic results support the general assumption that the premutation range of unstable CCTG stretches lies obviously between 25 and 75 CCTGs. However, the clinical significance of premutation alleles is still unclear. In the light of the two described families we suggest incomplete penetrance. Thus, as it was proposed for other repeat expansion diseases (e.g. Huntington´s disease), a fluid transition of penetrance is more likely rather than a clear cut CCTG number threshold.